Using podcast for EFL students in language learning - Indahsari, Dyan (Universitas Muhammadiyah Sidoarjo, 2020)
One of the popular products of technology created to support language learning is podcast. As a digital recording, podcast can be used to support English language learning, specifically on the listening skill. This study reviews the effects of using podcast in supporting language learning. The aim of this study is to introduce podcast as a tool for developing language skill. Podcast as a tool has the power to motivate students in learning English. This study reviewed 20 articles published around 2020-2010 to find the effects of using podcast in teaching English to EFL students. The result of this study showed that podcast can increase language ability, especially the listening skill. Furthermore, podcast can motivate students in learning language. Teachers are recommended to use podcast as an interesting technological tool to support language learning for Indonesian students. The students confirmed that podcast is fascinating when it is used in the learning of listening skill. Podcast is a potential choice as an English learning support and it allows teachers to incorporate technology in teaching. It is important to note that the intention is not to replace teacher’s presence with podcast. Therefore, it is suggested that in using podcast teachers should provide proper guidance for their students on how get its full potential. HIGHLIGHTS: Podcasts can be alternative media to foster innovation in English Language Teaching. Integrating podcast into the related curriculum and syllabi to support listening class helps provide more contextual and communicative materials.